Animals as Intentional Political Agents and God’s Warriors in Sign-Themed Qurʾānic Narratives - Kanwal, Aroosa (Worldviews, 2024)
Taking its cue from the Islamic Ecological Paradigm, deeply rooted in Islamic religious traditions, which emerged more than 1400 years ago, this paper reimagines the human-nonhuman relationship against the backdrop of the arguably assumed superiority of mankind in (Islamic) theological discourses. Using Qurʾānic narratives as a key point of divergence in the natural superiority of man within the idea of vicegerency, we argue that the Qurʾān’s egalitarian ethos presents animals as ‘intentional political agents’ (Pepper 2021: 30) independent of human intercession. This agency enables them to be key players in deciding the outcomes of political conundrums; in so doing, it also rebuts and destabilises arrogant anthropocentric presuppositions associated with the idea of vicegerency. We particularly read, in ‘signs themed’ Qurʾānic narratives, a dynamic relationship between humans and animals through the animal’s role as Allah’s warriors and agents against human oppressors and transgressors. Drawing on the Islamic Ecological Paradigm, Angie Pepper’s idea of intentional political agency and Sarra Tlili’s de-anthropocentric reading of the Qurʾān, we suggest that the Qurʾān robustly invites humans to reflect on the animal world by foregrounding animals as political agents while epitomising human accountability and responsibility towards them instead of establishing a relationship of dominance.